2020
DOI: 10.1007/s00217-020-03621-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on volatile marker compounds in cured loins fermented with Staphylococcus carnosus by brine injection

Abstract: In this study, the influence of low (5 °C), intermediate (15 °C) and high (25 °C) storage temperatures on the profile of volatile compounds of North European cured loins fermented with Staphylococcus carnosus strains was investigated. In this context, proteolytic activity, bacterial growth, key volatile compounds and sensory attributes were studied. In conclusion, storage temperature significantly affected the volatile marker compounds. A multiple regression indicated significant effects of seven volatile comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A wide variety of muscle products, including boneless meat, bone‐in parts, and fish fillets, are routinely injected with brine for curing to improve tenderness, juiciness, and flavor (Bosse et al., 2021). However, Mariutti and Bragagnolo (2017) have reported that salt added in meat and seafood can favor lipid oxidation.…”
Section: Conventional Antioxidant Delivery Methodsmentioning
confidence: 99%
“…A wide variety of muscle products, including boneless meat, bone‐in parts, and fish fillets, are routinely injected with brine for curing to improve tenderness, juiciness, and flavor (Bosse et al., 2021). However, Mariutti and Bragagnolo (2017) have reported that salt added in meat and seafood can favor lipid oxidation.…”
Section: Conventional Antioxidant Delivery Methodsmentioning
confidence: 99%
“…Amino acids are also important precursors of volatiles [ 17 ]. In our study, the sweet and over-oxidation aroma-related contributors such as organic acids (3-methyl-butanoic acid and n-decanoic acid), ketones (furaneol) and hydrocarbons (1,1-diethoxyethane and 2-ethoxy-propane) were increased after yellowing ( Figure 6 B), which could be mainly attributed to the Maillard reaction of amino acids and carbohydrates [ 18 , 19 , 20 , 21 ]. It was reported that caramel-like odorant furaneol is not only generated from Maillard reaction but also the hydrolysis product of bound furaneol [ 21 ].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, 2- and 3-methylbutanal produced by Leu and Ile can be oxidized to 2- and 3-methylbutanal by aldehyde dehydrogenase or reduced to 2- and 3-methylbutanol by alcohol dehydrogenase. These compounds produce malt, fruity, and sweaty flavors, which were identified as the key volatile compounds in cured ham and cured loin ( Bosse et al, 2021 ). In addition, the most abundant aldehydes in fermented sausage were non-anal formed by the oxidation of N-9 polyunsaturated fatty acids, which delivered the smell of carnation, citrus, and laurel ( Olivares et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%